Hypovolemia-related gastric tissue damage in the setting of upper gastrointestinal bleeding - Melih KARINCAOGLU; Yüksel SEÇKİN; Fehmi ATEŞ; Murat MM HARPUTLUOĞLU; Kadir BATÇIOĞLU; İrem Pembegül YİĞİT; R. İlyas ÖNER; Fatih HİLMİOĞLU (Turkish Journal of Gastroenterology, 2019)
-